2018
DOI: 10.1117/1.jbo.23.5.055005
|View full text |Cite
|
Sign up to set email alerts
|

Laser trap ionization for identification of human erythrocytes with variable hemoglobin quantitation

Abstract: An approach to an established technique that is potentially applicable for a more comprehensive understanding of the electrical properties of red blood cells (RBCs) is presented. Using a high-intensity gradient laser trap, RBCs can be singly trapped and consequentially ionized. The subsequent dynamics of the ionized cell allows one to calculate the charge developed and the ionization energy (IE) through a Newtonian-based analysis. RBCs with two different hemoglobin (Hb) types were ionized. The first sample was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…This study uses a new approach that uses laser trapping technique (LT) 17 for single cell ionization. We have recently demonstrated this approach in BT20 breast cancer cells 18 and human red blood cells 19,20 . This study uses a high-power infrared laser (at 1064 nm) to measure the radio sensitivity of 4T1 breast carcinoma cell lines treated by a naturally occurring compound, 2-Dodecyl-6-methoxycyclohexa-2, 5-diene-1, 4-dione (DMDD) extracted from the root of Averrhoa carambola L. Studies have shown that DMDD induces apoptosis of various human breast cancer cells through production of intracellular reactive oxygen species (ROS) and inhibition of NF-κB activation 21 .…”
Section: Introductionmentioning
confidence: 99%
“…This study uses a new approach that uses laser trapping technique (LT) 17 for single cell ionization. We have recently demonstrated this approach in BT20 breast cancer cells 18 and human red blood cells 19,20 . This study uses a high-power infrared laser (at 1064 nm) to measure the radio sensitivity of 4T1 breast carcinoma cell lines treated by a naturally occurring compound, 2-Dodecyl-6-methoxycyclohexa-2, 5-diene-1, 4-dione (DMDD) extracted from the root of Averrhoa carambola L. Studies have shown that DMDD induces apoptosis of various human breast cancer cells through production of intracellular reactive oxygen species (ROS) and inhibition of NF-κB activation 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Other potential nonthermal cell damages caused by linear optical excitation, nonlinear photonic effects and reactive oxygen species/singlet oxygen as a consequence of high-intensity near-infrared laser radiation need to be considered when trapping biological objects [16,87]. In optical trapping of human RBCs, except for the undesirable temperature rise, studies have revealed the OTs-induced deoxygenation of the trapping site on the RBC surface that is proportional to the trapping power [88] and have observed cell membrane ionization, inactivation and ejection from the trap by the thermally produced (radiometric) force induced by high power infrared laser trapping [89][90][91]. The observed RBC membrane rupture under high laser power (>500 mW) has been proven to be caused by the membrane electro-permeabilization and the resulting strong temperature gradient across the cell membrane induced by shape changes, rather than the total temperature rise (1.4 • C/100 mW) around the cell [89].…”
Section: Thermal and Nonthermal Damage To Biological Objects By Opticmentioning
confidence: 99%
“…With conventional OTs-based methods, diagnostic and therapeutic models of certain diseases, including sickle cell disorders, have been established based on the direct evaluation of RBC mechanical and physical properties [90,[122][123][124]. The efficacy of blood transfusion treatment in sickle cell anemia (SCA) has been evaluated by analyzing the mechanical response of transfused RBCs measured by conventional OTs [124].…”
Section: Applications Of Conventional and Polarized Otsmentioning
confidence: 99%
See 2 more Smart Citations